2017
DOI: 10.15252/embj.201796687
|View full text |Cite
|
Sign up to set email alerts
|

Sterol transfer, PI 4P consumption, and control of membrane lipid order by endogenous OSBP

Abstract: The network of proteins that orchestrate the distribution of cholesterol among cellular organelles is not fully characterized. We previously proposed that oxysterol-binding protein (OSBP) drives cholesterol/PI4P exchange at contact sites between the endoplasmic reticulum (ER) and the -Golgi network (TGN). Using the inhibitor OSW-1, we report here that the sole activity of endogenous OSBP makes a major contribution to cholesterol distribution, lipid order, and PI4P turnover in living cells. Blocking OSBP causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
234
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(273 citation statements)
references
References 62 publications
8
234
0
5
Order By: Relevance
“…It has been reported that inactivation of the ER‐localized adaptor proteins VAP‐A and VAP‐B leads to the accumulation of PI4P in endosomes due to the inability of the OSBP protein to transport PI4P from endosomes to the ER (Dong et al , ). Indeed, inhibition of OSBP by OSW1 was reported to induce accumulation of Golgi and endosomal PI4P (Mesmin et al , ). Therefore, we set out experiments to investigate the effect of OSW1 on endosomal PI4P.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that inactivation of the ER‐localized adaptor proteins VAP‐A and VAP‐B leads to the accumulation of PI4P in endosomes due to the inability of the OSBP protein to transport PI4P from endosomes to the ER (Dong et al , ). Indeed, inhibition of OSBP by OSW1 was reported to induce accumulation of Golgi and endosomal PI4P (Mesmin et al , ). Therefore, we set out experiments to investigate the effect of OSW1 on endosomal PI4P.…”
Section: Resultsmentioning
confidence: 99%
“…PI4P and PI4K2A were also found to organize important multi‐component signaling complexes on endosomes such as the lysosome‐related organelles complex 1 (BLOC‐1) and the Wiskott‐Aldrich Syndrome Protein and SCAR Homolog (WASH) complexes (Newell‐Litwa et al , ; Ryder et al , ; Dong et al , ). Lastly, PI4P levels on endosomes are also regulated by lipid‐transfer proteins of the OSBP family, suggesting that endosomal PI4P is utilized to drive the transport of lipids between the ER and endosomes (Dong et al , ; Mesmin et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of PI4KB by PKD at Ser294 mediates binding to 14-3-3 proteins, with this leading to an increase in PI4KB activity [22,23], that has been suggested to correspond with an increase in PI4KB stability [24]. In addition to regulatory protein interactions, PI4KB is predicted to contain an amphipathic lipid packing sensor (ALPS) motif at the C-terminus that mediates lipid binding to unsaturated membranes [9]. ACBD3 forms a direct, high-affinity interface with PI4KB that is mediated by a disorder-to-order transition in the N-terminus of PI4KB upon binding to the Q domain of ACBD3 [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple human pathogens manipulate PI4P levels to mediate their intracellular replication, including Legionella [3] and multiple picornaviruses [4,5]. PI4KB is localized at the Golgi and trans-Golgi network (TGN), with PI4P pools in the Golgi apparatus generated by both PI4K2A and PI4KB [9]. PI4KB is localized at the Golgi and trans-Golgi network (TGN), with PI4P pools in the Golgi apparatus generated by both PI4K2A and PI4KB [9].…”
Section: Introductionmentioning
confidence: 99%
“…FAPP2 transfers GlcCer to the trans-Golgi [112] as described in section 5.1 above. At membrane contact sites, OSBP directs cholesterol transfer from the ER to the trans-Golgi through coupled counter-transport of PI(4)P [142,186]. CERT transports ceramide from the ER to the trans-Golgi [187], thereby promoting SM and diacylglycerol synthesis.…”
Section: Golph3mentioning
confidence: 99%